Improving lifetime and availability for ad hoc networks to emergency and rescue scenarios - Torres Tandazo, R. (2017)
In disaster situations, where ad hoc mobile networks are normally used, the location and quantity of existing obstacles is random. Most existing mobility models have not been developed with consideration of the obstacles that exist in a disaster environment. This paper proposes two methods of mobility that realisticallyrepresent movement in an environment with obstacles. Unmarked Point Model (UPM) uses a high granularity strategy and Adjacency Vertex Model (AVM) uses a method that selects the shortest pathway. UPM consumes more resources than AVM to generate node mobility patterns in an ad hoc network, on a real map area of an urban area, where obstacles have been placed to simulate an emergency and rescue scenario. In addition, a comparative analysis of both models in its routing performance is done using AODV.